Internet connectivity disruption in Russia (Russia) - Voidly (2026)
CRITICAL severity disruption detected in Russia. Confidence: 70%. Data sourced from IODA.
Network Disruption Incident ID: RU-2026-0155
Keywords: internet disruption; RU; disruption; critical